(untitled) (Proceedings of International Educators Conference, 2024)
In this thesis, we describe quantitative determination of five flavonoids: Gallic acid, rutin, quercetin apigenin and kaempferol in two medicinal plants Urtica dioica L. and Melissa officinalis by high performance liquid chromatography (HPLC). Plant samples were extracted by optimized methods with 96% ethanol, and flavonoids separation was performed using a Perkin Elmer C18 column and gradient elution. The flavonoid concentrations were measured based on the calibration with standard solutions. Those results showed that the two species had different flavonoid profiles. In particular, Urtica dioica L. had the higher concentration of gallic acid, rutin and quercetin while Melissa officinalis revealed significant levels of rutin and kaempferol. These results offer an idea of the phytochemical content these to be a potentially used source for further natural product examination and characterization in pharmaceutical and nutraceutical sectors.